Mitigating interference via spatial and spectral nulling - Higgins, Thomas; Webster, Tegan; Shackelford, Aaron K (IET radar, sonar & navigation, 2014)
Phase-only transmit nulling may help the next generation of radar systems operate in an over-crowded radio frequency spectrum. The reiterative uniform weight optimisation (RUWO) algorithm generates constant modulus radar waveforms with spatial, frequency or space–frequency nulls for multiple-input multiple-output (MIMO) transmit arrays by utilising the maximum signal-to-interference plus noise ratio framework in a reiterative fashion. This study presents loop-back and open air experimental results, obtained using an eight-channel X-band coherent MIMO radar test bed, that demonstrate the use of RUWO to generate constant modulus waveforms that possess spatial and/or frequency nulls. The RUWO algorithm is first used to deterministically generate phase-only weights that produce spatial, frequency or space–frequency nulls at baseband in a loop-back configuration. The algorithm is then utilised to generate weights to produce spatial nulls, both deterministically and adaptively, for the full eight-channel test bed in an open air configuration. The deterministic and adaptive strategies are compared; results demonstrate that RUWO can be used to create spatial nulls and highlight the need for careful calibration of both the transmitter and the receiver.